PENGARUH HARGA, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK KEK PISANG VILLA DI OUTLET BOTANIA KOTA BATAM - Setiadji, Bayu; Lutfhi, Andi M. (Zona Manajerial: Program Studi Manajemen (S1), 2021)
In an era where technology is so sophisticated as it is today, it triggers very tight competition in the business world, plus the Covid-19 pandemic outbreak that originated in Wuhan, China in early 2020 until today has forced business actors to work even harder. All means and efforts are made so that their business can survive or even increase and can face increasingly fierce competition. The results of this study indicate that price, product quality and promotion have a simultaneous effect on purchasing decisions. Price, product quality and promotion together will have an influence on purchasing decisions.